Interventions to optimize antimicrobial stewardship - Nick J. Tinker; Rachel A. Foster; Brandon J. Webb; Souha Haydoura; Whitney R. Buckel; Edward A. Stenehjem (Cambridge University Press, 2021)
Developing and improving an antimicrobial stewardship program successfully requires evaluation of numerous factors. As technology progresses and our understanding of antimicrobial resistance grows, careful consideration should be taken to ensure that a program meets the needs of the institution and is achievable given the available resources. In this review, we explore fundamental initiatives and strategies for both new and established antimicrobial stewardship programs, including the specific areas to target and key elements required for sustainable implementation.